Coaching weightlifting in the age of sport technology - Swisher, A. (EWF Scientific Magazine, 2015)
An accelerometer would be hard pressed to identify when an athlete is burned out by training, coming down with a cold, or nervous about an upcoming contest. However, carefully chosen and implemented sport technology does have the potential to be a valuable supplemental source of information. Just as coaches must know tactical and biomechanical aspects of weightlifting, the profession is evolving such that coaches must be competent in using sport technology. To be most effective, coaches must first understand sport technology`s strengths and limitations and how to incorporate it into decision making.